RESILIENCE AND CONFLICT: THE ROLES OF COPRENEURSHIP, TRANSGENERATION, AND DARK SIDE OF FAMILY BUSINESS - Purwanto Purwanto; Eddy Madiono Sutanto; Nanik Kustiningsih (Jurnal Manajemen dan Kewirausahaan, 2024)
The present study aimed to examine the role of copreneurship, transgeneration, and the dark side with conflicts in and continuity of family-managed small and medium-sized enterprises (SMEs) or family businesses. Data was derived from 178 owners of batik SMEs, consisting of both those managed by spouses and those inherited. Data analysis was done using SEM-AMOS.22 and showed that (1) copreneurship positively related to family business conflicts; (2) transgeneration positively related to business management conflicts; (3) member family’s dark side positively related to conflicts; and (4) conflicts occurred due to tenuous family social identity (decreased copreneurship bond, transgenerational process failure and dark side) positively related to family business resilience. The present study also included control variables for business size and generational order in order to determine the extent and resilience of business continuity.